Spinal 1% 2-Chloroprocaine versus general anesthesia for ultra-short outpatient procedures: a retrospective analysis - Camponovo, Claudio (Acta Biomedica Atenei Parmensis, 2014)
Introduction: 2-Chloroprocaine is a local anesthetic with a very short half-life and a favorable evolution of spinal block for ultra-short outpatient procedures. The aim of this retrospective study is to evaluate the clinical impact of the introduction of spinal 1% 2-chloroprocaine compared to general anesthesia at the ARS Medica Clinic (Switzerland). Material and Method: We retrospectively evaluated the charts of all patients who underwent knee arthroscopy under general anesthesia (group GA) or spinal 2-chloroprocaine (group SA) between June 2012, when chloroprocaine was available for the first time, and December 2012. We collected the anesthesia time and the number of patients able to bypass the PACU. Moreover, we looked at hospital discharge time and we performed a pharmaco-economic analysis. Results: 61 charts were evaluated, 5 patients were excluded for insufficient data. The anesthesia time was comparable between the two groups. All patients in group SA were able to bypass the PACU versus only 18% in group GA. We observed a clinically significant reduction in terms of discharge time (203 vs 326 minutes) and cost of materials and employers involved patients’ care (53 vs 78 swiss franks) when spinal 1% 2-chloroprocaine was used. Conclusion: The right selection of the local anesthetic makes spinal anesthesia a suitable anesthetic technique for ultra-short outpatient procedures. If short acting local anesthetics are involved, spinal anesthesia could be competitive versus general anesthesia.